2011
DOI: 10.1136/bjophthalmol-2011-300640
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oxygen saturation is altered in diabetic retinopathy

Abstract: Retinal vessel oxygen saturation is higher in patients with diabetic retinopathy than in healthy controls. Possible explanations include shunting of blood through preferential channels, bypassing non-perfused capillaries in the capillary network. Parts of the retinal tissue may be hypoxic while blood in larger vessels has high oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
206
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(234 citation statements)
references
References 33 publications
21
206
0
7
Order By: Relevance
“…There are growing evidences suggesting that functional variations precede structural alterations [2,[4][5][6][7][8]. Thus, retinal metabolic rate of oxygen (rMRO 2 ), a hallmark of retinal metabolism, may be a key biomarker for early disease screening, evaluating disease severity, and monitoring response to therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are growing evidences suggesting that functional variations precede structural alterations [2,[4][5][6][7][8]. Thus, retinal metabolic rate of oxygen (rMRO 2 ), a hallmark of retinal metabolism, may be a key biomarker for early disease screening, evaluating disease severity, and monitoring response to therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal oxygen metabolism is a key factor in the pathogenesis of leading blinding diseases, including diabetic retinopathy (DR) and age related macular degeneration (AMD) [1][2][3][4]. There are growing evidences suggesting that functional variations precede structural alterations [2,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Diseases investigated so far include diabetic retinopathy (Hammer et al, 2009, Hardarson andStefansson, 2012b), glaucoma , Traustason et al, 2009) and retinal vein occlusion Stefansson, 2010, Hardarson andStefansson, 2012a). Ease of use and low variability paired with high sensitivity and specificity are essential for any diagnostic technology.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygenation of blood in retinal vessels can also be quantified noninvasively based on the differential light absorbance of oxyhemoglobin and deoxyhaemoglobin [114,115]. In human cross-sectional studies, oxygen saturation has been found to be higher in retinal venules of diabetic than non-diabetic subjects [114,116,117], and to decline further with increasing severity of diabetic retinopathy [114,117]. This may relate to loss of metabolically active retina, anatomical damage to retinal vessels, and arterio-venous shunt formation in the retina, all of which reducing oxygen consumption.…”
Section: Ocular-based Biomarkersmentioning
confidence: 99%